2012
DOI: 10.1016/j.soncn.2012.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers: Symptoms, Survivorship, and Quality of Life

Abstract: Objectives To review the evidence on a number of biomarkers that show potential clinical utility in the prediction of and treatment responsiveness for the four most common symptoms associated with cancer and its treatment (i.e., pain, fatigue, sleep disturbance, depression). Data Sources Review and synthesis of review articles and data-based publications. Conclusions A growing body of evidence suggests that sensitive and specific biomarkers will be available to assist clinicians with the assessment and man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 96 publications
(107 reference statements)
3
34
0
Order By: Relevance
“…We also observed that decreases in voluntary wheel running distance and speed were most pronounced during the late hours of the active phase, which is consistent with observations in mouse models of chemotherapy-induced fatigue [10, 18]. Moreover, this aspect of our model displays similarity to the clinical trajectory of fatigue following localized radiation therapy for non-metastatic cancer, where patients complain of worsening fatigue in the afternoon or evening hours [36, 37], strengthening its validity.…”
Section: Discussionsupporting
confidence: 88%
“…We also observed that decreases in voluntary wheel running distance and speed were most pronounced during the late hours of the active phase, which is consistent with observations in mouse models of chemotherapy-induced fatigue [10, 18]. Moreover, this aspect of our model displays similarity to the clinical trajectory of fatigue following localized radiation therapy for non-metastatic cancer, where patients complain of worsening fatigue in the afternoon or evening hours [36, 37], strengthening its validity.…”
Section: Discussionsupporting
confidence: 88%
“…This has been demonstrated in HIV patients , oncology patients and caregivers (Hohjoh et al, 1999;Miaskowski and Aouizerat, 2012;Wieczorek et al, 2003Wieczorek et al, , 2004.…”
Section: Insomnia or Sleep Disturbances And Inflammationmentioning
confidence: 88%
“…Pro-inflammatory cytokines and markers of their activity are also elevated in patients with cancer related fatigue (Barsevick et al, 2010). Pre-treatment cytokines and rises in cytokine levels after treatment may predict fatigue, and polymorphisms of the pro-inflammatory cytokines Il-1b, TNF-a and Il-6 are associated with cancer related fatigue, and fatigue in cancer caregivers (Miaskowski and Aouizerat, 2012). In addition, markers of inflammation and elevated levels of neutrophils and monocytes at baseline have been associated with fatigue after treatment (Saligan and Kim, 2012).…”
Section: Fatigue and Inflammationmentioning
confidence: 99%
“…Potentially, people at the greatest risk for high symptom burdens can be identified and treated early, thus preventing long-term sequela of untreated symptoms 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The use of biomarkers in symptom cluster research has the potential to assist in identifying who is at risk for experiencing a high symptom burden and treatment responders and nonresponses 33 . In LCA, biomarkers and genetic information could be used as covariates, indicator variables, or as a grouping variable to assist with uncovering the etiology of symptom clusters.…”
Section: Examples Of Latent Class Analysis In the Symptom Cluster Litmentioning
confidence: 99%